Using humor to maximize learning : the links between positive emotions and education - Morrison, Mary Kay, 1946- (Rowman & Littlefield Education, 2008)
The purpose of this book is to affirm, sustain and encourage educators in the practice of humor not only as a personal tool to optimize a healthy life style, but to maximize the benefits of humor in education. These benefits include current research-based data on the use of humor to nurture creativity, to increase the capacity for memory retention, to support an optimal learning environment and to build safe communities that reflect the relational trust necessary for collaborative learning.